DIGITAL TECHNOLOGIES AND THEIR ROLE IN THE ECONOMY OF THE FUTURE - Sheveleva O.; Kudaiberdieva K. (Vestnik Issyk-Kulʹskogo universiteta)
The article is devoted to the problems of the development of digitalization of the modern economy of Kyrgyzstan and its impact on economic processes that determine economic growth and social well-being. It is noted that digitalization does not become a significant factor in economic growth and has a contradictory effect on the increase and size of economic growth, further development of the theoretical foundations of analysis and measurement of economic growth in its conditions is required. The paper highlights the role and importance of process innovations in the course of digitalization, the widespread use of which may not lead to an increase in GDP. Digital technologies play a key role in the modern economy and will continue to form the basis of the economy of the future. They are becoming the driving force that determines the growth and development of various industries and enterprises. One of the main reasons for the success of digital technologies is their ability to significantly increase the efficiency of business processes, improve the quality of products and services, and improve customer interactions. It is shown that the business in the field of computer and information technology, as well as the sharing business based on the widespread use of Internet services and cloud technologies, is currently developing rapidly.